2021
DOI: 10.1371/journal.pone.0248895
|View full text |Cite|
|
Sign up to set email alerts
|

Personality trait predictors of adjustment during the COVID pandemic among college students

Abstract: Personality traits have been found to be related to a variety of health outcomes. The aim of this study was to examine how personality traits were associated with adjustment to the COVID pandemic in college students. The sample included 484 first-year university students (76% female) attending a northeastern university who completed the Big Five Inventory (BFI) personality assessment at the beginning of a semester that was disrupted by the COVID pandemic. Using a phone-based app, students completed daily ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 24 publications
3
63
2
Order By: Relevance
“…Our findings further demonstrate this association in adolescents. Our study also shows that, conversely, conscientiousness can lead to psychological problems: we found that conscientious individuals perceive more stress, which is inconsistent with previous studies ( Luo & Roberts, 2015 ; Rettew et al, 2021 ) in which conscientiousness was found to be a protective factor against perceived stress. This would seem to indicate that conscientiousness is a risk factor for stress levels during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings further demonstrate this association in adolescents. Our study also shows that, conversely, conscientiousness can lead to psychological problems: we found that conscientious individuals perceive more stress, which is inconsistent with previous studies ( Luo & Roberts, 2015 ; Rettew et al, 2021 ) in which conscientiousness was found to be a protective factor against perceived stress. This would seem to indicate that conscientiousness is a risk factor for stress levels during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has revealed that highly conscientious individuals are protected against the detrimental effects of anxiety, depression, and perceived stress ( Kotov et al, 2010 ; Tran et al, 2020 ). Moreover, recent work has examined the protective role of conscientiousness in the mental health-related issues of adults during the COVID-19 pandemic ( Nikčević et al, 2021 ; Rettew et al, 2021 ). However, less attention has been given to the specific issue of whether conscientious adolescents can better handle mental health-related issues when facing the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, subjects with neurotic personality seem to be at greater risk of higher worry levels. Neurotic people are typically more likely to experience and report negative emotions, also in COVID-19 pandemic context as confirmed by other studies (Rettew et al, 2021). Indeed, Aschwanden et al (2021) showed that high neuroticism levels were associated with more COVID-related concern, and worry related to the pandemic duration.…”
Section: Discussionsupporting
confidence: 69%
“…During COVID-19 pandemic, personality traits and in particular neuroticism emerged as one of the correlates of most of psychopathological outcomes and distress, although not as uniformly as expected (Kroencke et al, 2020;Lee and Crunk, 2020;Modersitzki et al, 2020;Somma et al, 2020). Unfortunately, very few studies investigated the association between personality traits and adjustment to COVID-19 with a longitudinal methodology (Rettew et al, 2021;Zacher and Rudolph, 2021). In these studies, authors revealed that higher levels of neuroticism favored increases in distress (Rettew et al, 2021;Zacher and Rudolph, 2021); higher levels in emotional stability anticipated decreases in perceived stressfulness of the COVID-19 pandemic (Zacher and Rudolph, 2021); while higher levels in agreeableness and conscientiousness anticipated increases in mood (Rettew et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, individuals lower in social anxiety were likely initially anxious and concerned about the uncertainty of not seeing others and missing out on important social events (e.g., weddings and graduation parties). For instance, a recent study found greater decreases in mood during the pandemic for young adults higher in extraversion, compared to those lower in extraversion (Rettew et al, 2021).…”
Section: Discussionmentioning
confidence: 98%